Quantitative Evaluation on the Effect of Experience Under Emergency Situations in NPP Main Control Room Based on Multimodal Data. (3rd April 2021) - Liu, Zhiyao; Zhao, Qichao; Zhang, Liming; Zhang, Xuegang; Fan, Jieyun; Wang, Qingju; Wu, Ping
Abstract: The safety of the main control room in a nuclear power plant is an important research topic with practical implications. In this study, we used virtual reality technology and multimodal data to investigate the effect of experience on operators' responses under emergency conditions. We asked participants to perform a series of tasks in a virtual fire emergency environment while simultaneously recording their behavioral, eye-tracking, and physiological data. The results showed a significant effect of experience on participants' behavioral performance, total fixation time, and skin electrical response. Participants from a high-experience group showed a longer total fixation duration and lower skin conductance level compared to those from a low-experience group. This suggested that experience could have an impact on operators' visual information extraction and mental stress under emergency situations in an NPP. Our study also provides a reference method for using virtual experimental settings and objective measurements for future human factor research in the main control room of an NPP.